2015
DOI: 10.1007/s00148-015-0544-1
|View full text |Cite
|
Sign up to set email alerts
|

On the heterogeneity of dowry motives

Abstract: Dowries have been modeled as pre-mortem bequests to daughters or as groom-prices paid to in-laws. These two classes of models yield mutually exclusive predictions, but empirical tests of these predictions have been mixed. We argue that the heterogeneity of findings can be explained by a heterogeneous world-some households use dowries as a bequest and others use dowries as a price. We estimate a model with heterogeneous dowry motives and use the predictions from the competing theories in an exogenous switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…On the other hand, customary cash dowry has a very significant positive effect. This is consistent with the suggestion that the cash component of the marital transfer from the bride's family is likely to be part of the groomprice for the groom's family rather than a bequest dowry for the bride (Arunachalam and Logan 2006).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, customary cash dowry has a very significant positive effect. This is consistent with the suggestion that the cash component of the marital transfer from the bride's family is likely to be part of the groomprice for the groom's family rather than a bequest dowry for the bride (Arunachalam and Logan 2006).…”
Section: Resultssupporting
confidence: 89%
“…Botticini's (1999) analysis of dowry in Renaissance Italy finds that rather than being just a groomprice or just a bequest, a dowry can actually perform both functions at the same time, compensating for the spouses' attributes on the one hand, while enhancing the bride's welfare on the other. A different kind of heterogeneity is suggested by Arunachalam and Logan (2006). Assuming that the two motives of bequest are mutually exclusive within a marriage, they find robust empirical evidence from a Bangladesh data set that both are at work in the population.…”
Section: Dowry In the Economics Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…So, they have to face domestic violence because men do not have to pay any cost for domestic violence (Chowdhury 2010). Arunachalam & Logan (2006) on their research established two models of dowry. One is the price model where the bride"s family gives dowry to the groom"s family to equilibrate the marriage market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another one is the bequest model when parents consider that, as their daughter is leaving home and do not inherent her father's property so, she should be given something as an alternative. This thing keeps women away from their father"s property (Arunachalam & Logan 2006). Bates et al (2004) have shown that there is a relationship between dowry and bride"s age.…”
Section: Literature Reviewmentioning
confidence: 99%